COVID-19 pandemic and safe dental practice: Need of the hour - G Anup Kumar; Remya Mohan; Darshan R Prasad Hiremutt; K Bala Vikhram (Wolters Kluwer Medknow Publications, 2020)
The COVID-19 pandemic has spread across the globe and is the greatest challenge faced by world nations today. The first outbreak of this disease occurred in a seafood market of Wuhan City, China. The community pattern of spread was alarming and has gripped the entire international society. The dentists and other health care professionals should take stringent measures to prevent the spread of infection while providing care. In this article, we discuss the etiology, clinical manifestations, route of transmission, general and specific infection control protocols to protect the dental health care professionals as well as patients from COVID 19 disease while providing emergency dental care.